2015
DOI: 10.1111/roiw.12162
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality and Political Polarization: Time Series Evidence Over Nine Decades

Abstract: Rising income inequality and political polarization have led some to hypothesize that the two are causally linked. Properly interpreting such correlations is complicated by the multiple factors that drive each of these phenomena, potential feedbacks between inequality and polarization, measurement issues, and statistical challenges for modeling non-stationary variables. We find that a more precise measure of inequality (the inverted Pareto-Lorenz coefficient) is statistically related to polarization while a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…The better fits of the House models may stem from its composition being more closely tied to very recent media or inequality conditions in contrast to the Senate whose more slowly shifting composition reflects conditions over the three preceding election cycles. Third, the TeaParty variable is more statistically significant in the Senate models, where it raises the political polarization index by about 8 points—similar in magnitude to the results found in Duca and Saving () who use a longer sample and focus on examining long‐run inequality effects on polarization . The difference between the House and Senate findings may reflect the fact that that more Senate seats were represented by moderates in the pre‐Tea‐Party era (perhaps because Senate “districts” cannot be gerrymandered).…”
Section: Are Inequality Media Fragmentation and Political Polarizatsupporting
confidence: 78%
See 2 more Smart Citations
“…The better fits of the House models may stem from its composition being more closely tied to very recent media or inequality conditions in contrast to the Senate whose more slowly shifting composition reflects conditions over the three preceding election cycles. Third, the TeaParty variable is more statistically significant in the Senate models, where it raises the political polarization index by about 8 points—similar in magnitude to the results found in Duca and Saving () who use a longer sample and focus on examining long‐run inequality effects on polarization . The difference between the House and Senate findings may reflect the fact that that more Senate seats were represented by moderates in the pre‐Tea‐Party era (perhaps because Senate “districts” cannot be gerrymandered).…”
Section: Are Inequality Media Fragmentation and Political Polarizatsupporting
confidence: 78%
“…We follow Duca and Saving () by including a control variable for the “Tea Party” phenomenon ( TeaParty ), equal to 1 for the 2011 and 2013 Congresses and 0 otherwise. Skocpol and Williamson () find that the Tea Party is associated with greater turnout among conservative portions of the electorate and has driven moderates of both parties out of Congress.…”
Section: Are Cable/pay Tv or Income Inequality Related To Polarizatiomentioning
confidence: 99%
See 1 more Smart Citation
“…The author also argues that as inequality goes up, poor voters participate less in elections (not examined explicitly) 8 , which leads to the diminishing vote shares of the left parties and forces them to move to the center. Duca and Saving (2016) show for the U.S. that elite polarization and income inequality coevolve. McCarty et al (2003, p. 4) observe in a detailed empirical study an increasing partyincome divide in the U.S. electoral landscape: "...we can see that the stratification of partisanship by income has steadily increased over the past 40 years, leading to an increasing cleavage between the parties" (see also McCarty et al, 2015).…”
Section: Drivers Of Polarizationmentioning
confidence: 99%
“…More recently, McCarty et al (2003, 2015 have noticed that economic inequality and political polarization have increased dramatically across the United States since the 1980s. Duca and Saving (2016) have shown in an econometric analysis that changes in inequality precede the changes in economic polarization in the U.S. although there is also some evidence for a reciprocal effect. Kuhn et al (2020) and others have shown additionally that wealth inequality has grown after the collapse of the Lehmann Brothers, a result that is also observable for currency crises in the developed world (Rübsam and Schneider 2020).…”
Section: Introductionmentioning
confidence: 99%